ANALISIS PENDAPATAN USAHATANI SAGU DI KECAMATAN TEBING TINGGI TIMUR KABUPATEN KEPULAUAN MERANTI - Deva Asmarandana; Djaimi Bakce; Didi Muwardi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2022)
Tebing Tinggi Timur District is a center for the development of sago plantations in Kepulauan Meranti Regency. Sago plantations in Tebing Tinggi Timur District have been cultivated for generations with local wisdom as an effort to optimize the land which is 80% peat. The purpose of this study was to determine the application of cultivation techniques and analyze the income of sago farming. The method used is descriptive analysis and analysis of agricultural income. The respondents consisted of 30 sago farmers. The results of the analysis of sago cultivation techniques showed that the sago cultivation techniques in Tebing Tinggi Timur District were not in accordance with the recommendations, while the income of sago farming showed a total profit of IDR 5,314,349.48 per year per ha. Keywords:Sago, Income Analysis, Cultivation Techniques.